The efficiency of electric cars for mitigating CO2 emissions in Poland - Walkowiak, Mikołaj (Research Papers in Economics and Finance, 2017)
This paper concerns the estimation of indirect CO2 emissions associated with the use of electric engines in Poland. The indirect production of exhaust fumes emitted by electric cars is determined by two factors: the engine’s power consumption and the volume of the emissions produced when generating power sold by distributors. The current structure of the Polish power system, which is the supplier of the prime mover for electric cars, uses mainly the conventional (high-emission) sources of energy. Thus, using electric cars becomes an indirect cause of the pollution in the atmosphere. Increasing the efficiency of the power production process along with limiting the emission level of the combustion process in conventional power plants is a fundamental and essential solution to reduce air pollution.